With Jesus in My Boat I Can Smile at the Storm: An Analysis of Poems and Short Stories by Children Living with Disabilities - Muganiwa, Josephine (Journal of disability & religion, 2016)
People with disabilities quickly notice the discrimination around them, but like everyone else, they need to go on in the business of living. The short stories and poems in the collections Small Friends and Other Stories and Poems by King George VI School and Centre for Physically Disabled Children reflect the coping mechanisms the disabled employ and what motivates them. Some of the poems appeal directly to God as acts of faith, while some point to nature. A literary analysis of this collection will be able to speak to reason and faith in the struggle to cope with socioeconomic and environmental challenges.